Acute Kidney Injury Is A Predictor Of Mortality In Patients Hospitalized With Covid-19: Nephrology - Rasul, Md Maqsudur; Emran Hossain; Miskat Joha; Dewan Mohaimenul Haque (KYAMC Journal, 2023)
Background: Common biomarkers used to determine the disease severity and prognosis of corona virus disease -19 (Covid-19) are well determined. Among these biomarkers only few can reliably predict disease outcome but they are not easily available and costly. So organ-specific functional status especially acute kidney injury (AKI) can be use as predictor of prognosis. Objective: To determine the kidney disease indicator as a marker in predicting the severe disease in COVID-19 patients. Material & Methods: We studied the health records for all purposively selected hospitalized Covid-19 patients for three months from 1st May to 31st July, 2020, at combined military hospital Dhaka, Bangladesh. Those who were more than 18 years old and hospitalized RT-PCR positive for COVID-19 patients were enrolled. Those having history of renal replacement therapy (RRT) and unwilling to participate were excluded from the study. Kidney disease significance between survivors and deceased were examined using Cox proportional hazard regression analysis. In-hospital death was ascertained by using the Kaplan-Meier method. Results: Total 470 patients were enrolled in this study. Mean age of study population was 54.7 (± 14.3) years and male to female ratio was about 2:1. Hypertension (51.91%) and diabetes mellitus (43.19%) were the most common co morbidity. During hospital stay 106 (22.55%) patients developed AKI. Total 23 (4.89%) patients were died of the total study population. Among them 19 (82.60%) had AKI. Mortality rate was significantly (P value<.001) higher among patients who developed AKI than those who did not (82.60 % vs 17.40%). Conclusion: Monitoring functional status of kidney should be given due importance to all Covid-19 patients even with mild disease. Early diagnosis and appropriate treatment of kidney injury and avoidance of nephrotoxic medications may help to reduce mortality and improve prognosis of COVID-19. KYAMC Journal Vol. 13, No. 04, January 2023: 192-197